Pengaruh Kompensasi dan Beban Kerja Terhadap Turnover Intention Karyawan pada Antic Sport Center Karawang - Nanda Zerlinda; Budi Rismayadi; Wike Pertiwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The objective of this study is to investigate the influence of compensation and workload on employee turnover intention at the antique sports center. This type of study applies quantitative with a population consisting of all employees of the Antic Sport Center, namely forty-five and a sample consisting of all employees of the Antic Sport Center, namely forty-five. The technique of sampling in this research uses a saturated sample, namely, all members of the population are sampled. Saturated sampling is often carried out when the population is relatively small, namely less than thirty people. The data collection technique used was questionnaires and observations of Antic Sport Center employees. In this study, the data analysis method used is multiple regression analysis, the data analysis of which is performed using the SPSS application program. Referring to the study results, the variable of compensation indivdiually has a negative and insignificant affect on turnover intention at the antique sports center, meaning that when compensation is low, employee turnover intention will increase. The partial workload variable on turnover intention at the Antic Sport Center has a significant positive influence. This means that when the workload is high, the level of employee turnover intention increases, and simultaneously the compensation and workload variables on turnover intention at the Antic Sport Center have a significantly positive influence, meaning this reveals that the compensation and workload variables simultaneously will increase employee turnover intention.